Description of Students' Level of Knowledge, Attitudes and Behavior SMA Santo Thomas 1 Medan Regarding Prevention of Sexually Transmitted Infections in 2022 - Rudyn R Panjaitan (Sean Institute, 2022)
Sexually Transmitted Infections (STIs) are various infections that can be transmitted from one person to another through sexual contact. Most sufferers of sexually transmitted diseases are aged 15-49 years. In 2019, the North Sumatra Provincial Health Service reported a significant increase in the incidence of sexually transmitted infections (STIs) in recent years. The increasing trend in the spread of this disease is caused by deviant sexual behavior and the presence of premarital and extramarital sexual relations which is quite high due to the low level of knowledge about sexually transmitted diseases. This study aims to determinedescription of the level of knowledge, attitudes and behavior of students at SMA Santo Thomas 1 Medan regarding the prevention of sexually transmitted infections. The research was conducted using a descriptive research method with a cross-sectional design. The sample for this research was 215 students from SMA Santo Thomas 1 Medan in 2022. Data analysis was carried out using total sampling. The results of testing the level of knowledge, attitudes and behavior regarding STI prevention show that the majority of students at SMA Santo Thomas 1 Medan have knowledge in the good category (60%), attitudes in the good category (94.9%), and behavior in the good category. (41.9%). The level of knowledge, attitudes and behavior of SMA Santo Thomas 1 Medan students regarding STI prevention is good.